A Rapidly Growing Abdominal Mass: Desmoid Tumor in Pregnancy - Mateo G. Leon; Hind N. Moussa; Malahat Movahedian; Oscar A. Viteri; Monica Longo; Baha M. Sibai (Thieme Medical Publishers, Inc., 2015)
Abstract Background Desmoid tumors are benign soft tissue tumors that locally invade adjacent tissue. There is a paucity of reports describing the rapid growth of these tumors during pregnancy. Case A giant desmoid tumor arising from the left abdominal wall of a young female patient with rapid growth during pregnancy is described. Preoperative evaluation included ultrasonography and magnetic resonance imaging. Decision made by a multidisciplinary team was not to intervene before birth, and abdominal delivery at term was accomplished. Conclusion Desmoid tumors should be part of the differential diagnosis in an abdominal wall tumor of rapid growth during pregnancy. Future studies are needed for better understanding of the pathogenesis, diagnosis, and treatment of desmoid tumors in pregnant women.